A bigger prize : how we can do better than the competition - Heffernan, Margaret, 1955- (PublicAffairs, 2014)
"A leading business strategist and former CEO draws lessons from long-successful companies to dispel the myth that competition has to be a zero-sum game, showing how companies that foster collaboration and a healthy interdependency are more likely to become --and remain-- significant leaders in their field"--